2022
DOI: 10.3390/su14041961
|View full text |Cite
|
Sign up to set email alerts
|

Food Waste, Attitudes and Preferences of Young Females: A Case Study in Saudi Arabia

Abstract: Investigations of attitudes towards food waste and preferences of policies that affect sustainability has increased rapidly over the past few decades. Most research on food waste, however, has been undertaken mainly in the developed countries with very few in the developing countries. It is very important therefore to investigate food waste and attitudes towards sustainability in developing countries, especially since a huge amount of carbon emissions and other pollutants occur in the developing countries. Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Analysis of participants levels of practice based on the estimated mean values, the evaluation is classi ed as "Very good" if the mean is greater than 4.5, "Good" if the mean ranges from 4 to 4.49, "Fair" for the mean value range from 3.5 to 3.99, and "Poor" if the mean is less than 3.5. The results of average values in table (5) implied that the statement "I am ready to classify solid waste at the source (P07)" obtained the highest weighted mean (4.81). Two attitudes also got very good ranks (mean > 4.5).…”
Section: Analysis Of Practice Situationmentioning
confidence: 98%
See 3 more Smart Citations
“…Analysis of participants levels of practice based on the estimated mean values, the evaluation is classi ed as "Very good" if the mean is greater than 4.5, "Good" if the mean ranges from 4 to 4.49, "Fair" for the mean value range from 3.5 to 3.99, and "Poor" if the mean is less than 3.5. The results of average values in table (5) implied that the statement "I am ready to classify solid waste at the source (P07)" obtained the highest weighted mean (4.81). Two attitudes also got very good ranks (mean > 4.5).…”
Section: Analysis Of Practice Situationmentioning
confidence: 98%
“…Respondents were asked to rate the likelihood of their practice through seven statements with ve Likert scale choices. The choices were "Strongly disagree" (1), "Disagree" (2), "Neutral" (3), "Agree" (4), and "Strongly agree" (5).…”
Section: Analysis Of Practice Situationmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that even though the students showed a great deal of awareness and concern about the environmental sustainability of the campus, they lacked interest and willingness to participate in initiatives toward achieving sustainability. Alsawah et al [29] designed a questionnaire that consists of 5 sections and contains 23 questions to collect data from 199 female students at Princess Norah Bint Abdulrahman University. The questionnaire evaluated the attitudes and preferences of students towards food waste in their community rather than in the university.…”
Section: Introductionmentioning
confidence: 99%